2020
DOI: 10.1128/aem.00049-20
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Glycogen Provides Short-Term Benefits in Changing Environments

Abstract: Changing nutritional conditions challenge microbes and shape their evolutionary optimization. Here, we used real-time metabolomics to investigate the role of glycogen in the dynamic physiological adaptation of Escherichia coli to fluctuating nutrients following carbon starvation. After the depletion of environmental glucose, we found significant metabolic activity remaining, which was linked to rapid utilization of intracellular glycogen. Glycogen was depleted by 80% within minutes of glucose starvation and wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 41 publications
6
46
0
1
Order By: Relevance
“…In this study, we investigated the influences of glycogen on the survival abilities of E. coli BW25113 and its single-gene mutants under starvation, low temperature, desiccation, and oxidative stress. As an important energy reserve, bacterial glycogen was able to provide both short-term benefits in changing environments (Sekar et al, 2020) and long-term persistence in the environment (Bourassa and Camilli, 2009). Our study further confirmed that glycogen over-accumulating strains survived much better than wild-type and other mutated strains under starvation conditions, even though glycogen utilization was disrupted.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, we investigated the influences of glycogen on the survival abilities of E. coli BW25113 and its single-gene mutants under starvation, low temperature, desiccation, and oxidative stress. As an important energy reserve, bacterial glycogen was able to provide both short-term benefits in changing environments (Sekar et al, 2020) and long-term persistence in the environment (Bourassa and Camilli, 2009). Our study further confirmed that glycogen over-accumulating strains survived much better than wild-type and other mutated strains under starvation conditions, even though glycogen utilization was disrupted.…”
Section: Discussionsupporting
confidence: 74%
“…Especially, the short-term storage compound glycogen seems to be important to maintain metabolic activity directly after removal of a carbon source. This result was supported by a study that used metabonomics to compare metabolism of wild-type E. coli and a glycogen deficient mutant (Sekar et al 2020). The study showed that glycogen utilization plays an important role in providing energy during the very early phase of carbon starvation and that this enabled non-growing E. coli to quickly resume growth when glucose became available.…”
Section: Growth Arrest Due To Starvationmentioning
confidence: 82%
“…Furthermore, the genome of LB57 encodes 33 genes classified as GT3, absent in the other isolates, involved in glycogen synthesis ( Figure 4 ). This may indicate that this strain has evolved to use glycogen for energy reserve, as previously observed in other bacteria, resulting in higher resistance to starvation and improved ecological fitness [ 12 , 36 ]. GT3 genes have been previously observed in L. crispatus strains isolated from vaginal microbial populations characterized by lactobacilli dominance [ 12 ].…”
Section: Resultsmentioning
confidence: 73%